Differential Expression of Putative Ornithodoros turicata Defensins Mediated by Tick Feeding - Brittany A. Armstrong; Brittany A. Armstrong; Alexander R. Kneubehl; Alexander R. Kneubehl; Robert D. Mitchell; Aparna Krishnavajhala; Pete D. Teel; Adalberto A. Pérez de León; Job E. Lopez; Job E. Lopez (Frontiers in Cellular and Infection Microbiology, 2020)
Additional research on soft ticks in the family Argasidae is needed to bridge the knowledge gap relative to hard ticks of the family Ixodidae; especially, the molecular mechanisms of Ornithodoros biology. Ornithodoros species are vectors of human and animal pathogens that include tick-borne relapsing fever spirochetes and African swine fever virus. Soft tick vector-pathogen interactions involving components of the tick immune response are not understood. Ticks utilize a basic innate immune system consisting of recognition factors and cellular and humoral responses to produce antimicrobial peptides, like defensins. In the present study, we identified and characterized the first putative defensins of Ornithodoros turicata, an argasid tick found primarily in the southwestern United States and regions of Latin America. Four genes (otdA, otdB, otdC, and otdD) were identified through sequencing and their predicted amino acid sequences contained motifs characteristic of arthropod defensins. A phylogenetic analysis grouped these four genes with arthropod defensins, and computational structural analyses further supported the identification. Since pathogens transmitted by O. turicata colonize both the midgut and salivary glands, expression patterns of the putative defensins were determined in these tissues 1 week post engorgement and after molting. Defensin genes up-regulated in the tick midgut 1 week post blood feeding were otdA and otdC, while otdD was up-regulated in the midgut of post-molt ticks. Moreover, otdB and otdD were also up-regulated in the salivary glands of flat post-molt ticks, while otdC was up-regulated within 1 week post blood-feeding. This work is foundational toward additional studies to determine mechanisms of vector competence and pathogen transmission from O. turicata.